Antibacterial peptides from Hadruroides mauryi and Centruroides margaritatus venom - Escobar, Enrique (2008)
In this work, we describe antibacterial peptides from Hadruroides mauuryi and Centruroides margaritatus scorpion venom, isolated by ionic exchange chromatography with 0,05M ammonium acetate buffer pH 7. H. mauryi venom (44,4 mg) was separated in 7 protein peaks. IV peak inhibited growth of Escherichia coli, Pseudomona aeuginosa and Bacillus cereus: V peak affect to P. aeruginosa and B. cereus, and VI peak have activity on B. cereus. C. margaritatus venom (50,6 mg) was also separated en 7 protein peaks. II peak inhibited growth of Staphylococcus aureus; III, IV, V and VI peaks affect to S. aureus , P. aeruginosa and B. cerus; and finally VII peak affect to P. aeruginosa. All isolated peptides were of basic pH, with exception of II peak from C. margaritatus. In addition, all peptides have not hemolitic activity.